A Biomechanical Evaluation of a 2-Suture Anchor Repair Technique for Thumb Metacarpophalangeal Joint Ulnar Collateral Ligament Injuries. (September 2018) - Gil, Joseph A.; Chambers, Alison; Shah, Kalpit N.; Crisco, Joseph J.; Got, Christopher; Akelman, Edward
Background: A complete thumb ulnar collateral ligament (UCL) repaired with 1-suture anchor has been demonstrated to be significantly weaker compared with the intact UCL. The objective of this study is to test the biomechanical strength of a 2-anchor thumb UCL repair.Methods: Nine paired fresh-frozen hands were used for this biomechanical analysis. One thumb from each pair was randomized to the control group and one to the repair group. In the control group, the UCL was loaded to failure in tension. In the repair group, the UCL was dissected off of the proximal phalanx, subsequently repaired with a 2-anchor technique, and then tested to failure.Results: The mean yield load was 342 N (95% confidence interval [CI], 215-470 N) in the control group and 68 N (95% CI, 45-91 N) in the repair group. The mean maximum load at failure was 379 N (95% CI, 246-513 N) in the control group and 84 N (95% CI, 62-105 N) in the repair group. The mean stiffness was 72 N/m (95% CI, 48-96 N/m) in the control group and 17 N/m (95% CI, 13-21 N) in the repair group. The mean displacement at failure was 7.8 mm (95% CI, 7-9 mm) in the control group and 7.8 mm (95% CI, 7-9 mm) in the repair group.Conclusions: The 2-anchor repair technique we tested does not acutely reestablish the strength of the insertion of the native insertion of the UCL with this technique.